Analysis of deliverability data in shale gas reservoirs: pseudo-pressure and pressure employed. Issue 4 (4th July 2019) - Zhao, Chaojie; Li, Jun; Zhang, Hui
ABSTRACT: Forecasting deliverability in shale gas reservoirs accurately has received much attention in the industry in recent years. Most wells in shale gas reservoirs are horizontal with multiple fractures, and it has been widely recognized that the dominant early flow regime is usually long-duration transient flow. The most popular method for analyzing linear flow is the plot of rate-normalized pressure versus square root of time, where the pseudo-pressure is employed for gas. However, the pseudo-pressure employed approach is difficult to handle by hand than the pressure employed approach. The purpose of this work is to evaluate the accuracy of pseudo-pressure employed method for analyzing gas rate in shale gas reservoirs, and establish which method is the most simple and accurate for reserve estimation. Based on a number of numerically simulated cases, comparisons between the pseudo-pressure and pressure employed methods for estimating gas rate are made. It is shown that the pressure employed method yields the gas rate that not quite accurately match the simulated values, however, as the same general parameters, the pseudo-pressure employed method really does not improve this inaccuracy. Accordingly, the pressure employed approach is a good and simple method for forecasting gas rate. In addition, depending on the simple hand method, a modification approach is proposed by incorporating constant factors to forecast the gas rate with more confidence. This work will provide an efficient guidance to assist analysts in evaluating hydrocarbon deliverability rapidly and efficiently in shale gas reservoirs.